Kinematic comparison of the wrist movements that are possible with a biomechatronics wrist prosthesis and a body-powered prosthesis: a preliminary study - Abd Razak, N.A.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar (2012)
Purpose: This study examined the kinematic differences between a body-powered prosthesis and a biomechatronics prosthesis as a transradial amputee performed activities that involve flexion/extension and supination/pronation of the wrist. Method: The subject's wrist movements were calculated and compared as he completed a wrist range of motion test involving simulated flexion/extension and supination/pronation. Results: The results revealed that, under the test conditions, the body-powered prosthesis limits an individual's ability to complete four different tasks of wrist movement especially when it comes to complete the supination/pronation movement. Conversely, while using biomechatronics wrist prosthesis, the user was able to compensate for limited wrist motion through an ability to achieve a greater range of wrist movement. Conclusions: The biomechatronics wrist prosthesis provides a greater degree of freedom of wrist flexion/extension and supination/pronation movements.